2008
DOI: 10.1111/j.1439-0418.2007.01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Beauveria bassiana against the strawberry pests, Lygus lineolaris, Anthonomus signatus and Otiorhynchus ovatus

Abstract: There are several insect species causing serious economic losses in strawberry, Fragaria vesca L., productions. In Quebec, Canada, the tarnished plant bug, Lygus lineolaris (Palisot de Beauvois), the strawberry bud weevil clipper, Anthonomus signatus (Say) and the strawberry root weevil, Otiorhynchus ovatus (L.) are the most important pests. We tested the susceptibility of these pests to the entomopathogenic fungus Beauveria bassiana under laboratory conditions. Sixteen isolates were evaluated for their insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 50 publications
4
7
0
5
Order By: Relevance
“…Results of the present research showed that the repeated use of B. bassiana caused a significant reduction in the pest population than uncontrolled plot. These results were supported by the findings of Sabbahi et al (2008) since the application of B. bassiana as a conidial spray under field conditions requires tolerance of the conidia to UV light, low relative humidity, and the ability to persist on plant foliage. Hence, multiple applications can compensate for the pathogen's intolerance to suboptimal field conditions.…”
Section: Suppressed Infestation (%)supporting
confidence: 79%
See 1 more Smart Citation
“…Results of the present research showed that the repeated use of B. bassiana caused a significant reduction in the pest population than uncontrolled plot. These results were supported by the findings of Sabbahi et al (2008) since the application of B. bassiana as a conidial spray under field conditions requires tolerance of the conidia to UV light, low relative humidity, and the ability to persist on plant foliage. Hence, multiple applications can compensate for the pathogen's intolerance to suboptimal field conditions.…”
Section: Suppressed Infestation (%)supporting
confidence: 79%
“…Current study revealed that integration of B. bassiana and Imidacloprid along with Potassium silicate increase the efficacy after different exposure time intervals and significantly reduced the infestation losses as well as increased yield which showed the compatibility of entomopathogenic fungi with systemic insecticides. Because Potassium silicate and B. bassiana alone did not gave as satisfactory results as used in combinations, similar results were found for the entomopathogenic fungi with different pesticides (Milner et al, 2003;Sabbahi et al, 2008;Feng et al, 2003;Gatarayiha et al, 2010;Jiang et al, 2012). Similar synergistic effects were observed against Colorado potato beetle by applying entomopathogenic fungi B. bassiana with synthetic chemicals (Anderson et al, 1989).…”
Section: Suppressed Infestation (%)supporting
confidence: 69%
“…), the tarnished plant bug, Lygus lineolaris, the strawberry bud weevil, Anthonomus signatus , and the strawberry root weevil, Otiorhynchus ovatus (Sabbahi et al. ,b), the white pine weevil, Pissodes strobi (Trudel et al. ), the pine shoot beetle, T. piniperda (Lavallée et al.…”
Section: Discussionmentioning
confidence: 99%
“…An individual isolate can exhibit a substantially restricted host range (Inglis et al 2001). Moreover, isolates recovered from a closely related species are generally more virulent than isolates from non-related species (Sabbahi et al 2008).…”
Section: Resultsmentioning
confidence: 99%